2011
DOI: 10.1002/ibd.21509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli isolated from gut biopsies of newly diagnosed patients with inflammatory bowel disease

Abstract: Adherent invasive E. coli are present at first diagnosis, suggesting that they may have a role in the early stages of disease onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 53 publications
4
56
4
2
Order By: Relevance
“…A growing body of work indicates genetic and phenotypic diversity among AIEC isolated from human adults with IBD (7,27,35,44,48), children with Crohn's disease (4,5), and companion animals (49,50). This diversity suggests that host pathways might select for certain AIEC genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work indicates genetic and phenotypic diversity among AIEC isolated from human adults with IBD (7,27,35,44,48), children with Crohn's disease (4,5), and companion animals (49,50). This diversity suggests that host pathways might select for certain AIEC genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) has become a common method for typing pathogenic E. coli strains (13)(14)(15)(16)(17)(18) and establishing their relatedness. A small number of housekeeping genes are sequenced and assigned a unique allele, and the allelic profile of the housekeeping genes can be used to give an isolate a sequence type (e.g., E. coli O104:H4 is ST678 and many STEC O157:H7 isolates are ST11, based on the MLST databases [see below]).…”
Section: Microbiology Isolation and Typing Of E Colimentioning
confidence: 99%
“…AIEC has been implicated in inflammatory bowel diseases in humans and animals, including CD in humans and granulomatous colitis in boxer dogs, chickens, and turkeys (858,859). Human studies have found that AIEC colonizes the intestinal mucosae of CD patients and is associated with both early and chronic lesions, suggesting that AIEC may initiate disease as well as contribute to chronic inflammation (17,843,860). CD presents with abdominal pain, fever, and bowel obstruction or diarrhea with the presence of blood and/or mucus (861).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…It has been hypothesized that the LF82 genome has evolved from those of extraintestinal pathogenic E. coli (ExPEC) B2 strains by the acquisition of Salmonella and Yersinia isolated or clustered genes or predicted coding sequences located on plasmids and at various loci on the chromosome (441). Following the isolation of the prototype AIEC LF-82 strain, other CD-and UC-associated AIEC strains have been isolated and characterized (442)(443)(444)(445)(446)(447)(448)(449). The results indicate that AIEC isolated from IBD patients has not evolved from a single ancestral background but corresponds to a group of bacteria that have been able to take advantage of an "IBD microenvironment" and probably share some common genes with ExPEC (446).…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%